Patient and injection partner perspectives on barriers and facilitators to home-based administration of long-acting injectable antiretroviral therapy - Alicia T. Bolton; Beth Bourdeau; Greg Rebchook; Jonathan Van Nuys; Erin Moore; Kate Buchacz; Jesse O’Shea; Parya Saberi (PLoS ONE, 2026)
Long-acting injectable antiretroviral therapy (LAI-ART) offers an alternative to daily oral treatment but is typically administered in clinics, which can create barriers for some people with HIV (PWH). Home-based administration by trained treatment buddies (TBYs)—trusted partners, friends, or family members—has not been systematically studied. We conducted semi-structured interviews with 31 participants (16 PWH and 15 TBYs) across 4 HIV clinics in the San Francisco Bay Area between June 2024 and April 2025. Guided by the Consolidated Framework for Implementation Research (CFIR), interviews explored anticipated facilitators, barriers, and training needs for home-based LAI-ART. Participants identified several anticipated benefits of home-based LAI-ART, including increased convenience, reduced transportation burdens, enhanced privacy, comforting and emotionally supportive care, and opportunities to foster empowerment and shared responsibility between PWH and TBYs. Key barriers included concerns about medication storage and delivery logistics, maintaining reliable injection schedules, needlestick safety, and the readiness and confidence of TBYs. Participants emphasized the need for hands-on training, ongoing support, and clear protocols to ensure safe, acceptable, and effective home-based administration. These findings underscore the importance of proactive planning and tailored support in addressing both the technical and emotional dimensions of home-based LAI-ART. Anticipating these needs can facilitate the successful implementation and expand access to person-centered HIV care.